Antifungal and post-antifungal effects of chlorhexidine, fluconazole, chitosan and its combinations on Candida albicans - Azcurra, A. I. (2011)
Objective: The aim of this work was to assess the antifungal and post-antifungal effects of chlorhexidine, fluconazole, chitosan and its combinations on virulence factors of Candida albicans. Study Design: Ten isolated strains of Candida albicans obtained from 10 patients with oral candidiasis and a collection strain of C. albicans were treated with antifungal agents in different concentrations or combinations of them. Virulence factors analyzed were the cell surface hydrophobicity, the germinative tube development, the phospholipase activity and the post-antifungal effect of that exposure. Results: Virulence factors of the isolated strains obtained from patients together with the collection strain showed significant decreases with the different antifungal treatments, except for hydrophobicity and phospholipase activity. The development of germinative tube was the most sensitive factor to all the antifungal agents used. Untreated strains as well as the ones treated with antifungal agents showed a positive correlation among the virulence factors analyzed. No synergic effects arose from the combinations of the used drugs. Conclusions: C. albicans isolated strains from patients showed high phospholipase activity and germinative tube production, which corroborates their capacity to infect the oral mucosa and the high prevalence of species. As a whole, our results imply that short exposures to sub-inhibitory concentrations of the antifungal agents under analysis, isolated or combined, can modulate the way virulence factors get manifested, thus decreasing their pathogenicity.